2017
DOI: 10.1002/celc.201700588
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of Oxygen on PdPt Alloy Nanocubes in Alkaline and Acidic Media

Abstract: The electrochemical kinetic behavior of the oxygen reduction reaction (ORR) on PdPt alloy nanocubes of various compositions is investigated in 0.1 M KOH and 0.1 M HClO4 solutions, adopting the rotating disk electrode (RDE) configuration. The PdPt nanocubes are prepared in the presence of polyvinylpyrrolidone and identified by using transmission electron microscopy (TEM). TEM images reveal that the PdPt alloy nanoparticles have a preferential cubic shape and the average particle size is approximately 8–10 nm. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
(94 reference statements)
1
9
0
Order By: Relevance
“…The RDE-LSV curves obtained for the Pt-SWCNTs and Pt-MWCNTs were mostly coincident, and the half-wave potential definitely shifted toward positive, compared to that of the commercial Pt–C, by 38 mV, exhibiting the higher electrocatalytic activities of the Pt-CNTs prepared in this study. Although such potential differences were also apparent in the Tafel plots, all plots gave a slope of 60 mV dec –1 in the low-current density region and a slope of 120 mV dec –1 in the high-current density region as many other studies have reported. ,, As mentioned previously, we assume that a trace amount of IL remains on the catalysts prepared by the IL-sputtering method, which works as an adhesive bond for the adsorption of Pt NPs on a carbon support. This assumption does not rule out the possibility that the IL is also attached to the surfaces of the Pt NPs.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The RDE-LSV curves obtained for the Pt-SWCNTs and Pt-MWCNTs were mostly coincident, and the half-wave potential definitely shifted toward positive, compared to that of the commercial Pt–C, by 38 mV, exhibiting the higher electrocatalytic activities of the Pt-CNTs prepared in this study. Although such potential differences were also apparent in the Tafel plots, all plots gave a slope of 60 mV dec –1 in the low-current density region and a slope of 120 mV dec –1 in the high-current density region as many other studies have reported. ,, As mentioned previously, we assume that a trace amount of IL remains on the catalysts prepared by the IL-sputtering method, which works as an adhesive bond for the adsorption of Pt NPs on a carbon support. This assumption does not rule out the possibility that the IL is also attached to the surfaces of the Pt NPs.…”
Section: Resultssupporting
confidence: 64%
“…Carbon-supported Pt or Pt alloy nanoparticles (NPs) are still the best catalysts for polymer-electrolyte fuel cells (PEFCs). This is because the sluggish oxygen reduction reaction (ORR) of the PEFCs requires particularly high Pt loads, although many attempts have been made to develop non-precious-metal catalysts because of the price and the preference for abundant resources. It is, however, known that even carbon-supported metal catalysts with sufficient activity suffer from stability issues that are mainly caused by the corrosion of the carbon support, which detaches the metal NPs, and by particle growth due to sintering. , To overcome such issues, choosing a carbon support with high durability is one key strategy, and a carbon nanotube (CNT) composed of sp 2 carbons is considered to be a promising candidate because it has an extremely inert surface that prevents the corrosion. Metal catalyst deposition is possible even on such an inert surface by chemical means , and physical means such as metal sputtering, , but a weak interaction allows metal particles to easily migrate, resulting in particle growth. , To firmly fix the metal catalyst, it is necessary to pretreat the surface of the CNT, for example, through the chemical generation of functional groups and polymer modification, both of which are conducted to create scaffolds to anchor the metal particles. However, it is important to note that the former is accompanied by the partial destruction of the sp 2 structure, which sacrifices the intrinsic stability of the CNT.…”
Section: Introductionmentioning
confidence: 99%
“…The use of three‐dimensional Pt‐on‐Pd bimetallic quite rough (branched) nanoparticles on reduced graphene oxide (rGO) (Pt‐on‐Pd/rGO) has been found to lead to relatively greater improvements in ORR activity compared to PtPd/rGO, Pt/rGO, Pd/ rGO, PtPd nanoparticles/rGO, Pt black, Pd black, Pt/C, and Pd/C electrocatalysts . In addition, high ORR activity of Pt−Pd alloys has been reported by Jukk et al …”
Section: Introductionmentioning
confidence: 90%
“…However, the lack of desirable high‐performance electrocatalysts to boost both oxygen reduction reaction (ORR) during discharging and oxygen evolution reaction (OER) during charging, becomes a bottleneck to achieve this goal . Precious metals (e. g., Pt, Ru, Ir) have been found to be the most active electrocatalysts for single ORR or OER . Disappointingly, these metals still face the great challenge to achieve sufficient bifunctional activity for ORR and OER simultaneously, not to mention their high costs and poor durability.…”
Section: Introductionmentioning
confidence: 99%